Penerapan Arsitektur Pakpak Pada Perancangan Hotel Resort di Silalahi - Saraan, Iskandar Jalil; Moerni, Saufa Yardha (Universitas Medan Area, 2025)
Silalahi Village, located in Dairi Regency, North Sumatra, has become a popular tourist destination as part of the Toba Caldera Geopark area, which has been designated as a UNESCO Geopark. The area has great potential to attract both local and foreign visitors, and since the COVID-19 pandemic, there has been an increase in tourism. To support this growth, more resort hotels are being built in the Toba Caldera tourist area, including in Silalahi. A resort hotel in Silalahi will help further to develop the area as a potential tourist destination. The resort hotel in Silalahi was designed using architectural methods incorporating a neo-vernacular approach to preserve the surrounding cultural and natural environment. This approach drew inspiration from the traditional houses of the Pakpak ethnic group, the majority population in Dairi Regency. The resort hotel incorporates elements of Pakpak traditional house architecture into its design, such as the roof shape, building on stilts, and decorative ornaments on the building façade